Cheap beeps - Efficient synthesis of sinusoids and sweeps in the MDCT domain - Disch, Sascha; Schubert, Benjamin; Edler, Bernd (Proceedings of the IEEE 2013 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2013)
Modern transform audio coders often employ parametric enhancements, like noise substitution or bandwidth extension. In addition to these well-known parametric tools, it might also be desirable to synthesize parametric sinusoidal tones in the decoder. Low computational complexity is an important criterion in codec development and essential for acceptance and deployment. Therefore, efficient ways of generating these tones are needed. Since contemporary codecs like AAC or USAC are based on an MDCT domain representation of audio, we propose to generate synthetic tones by patching tone patterns into the MDCT spectrum at the decoder. We demonstrate how appropriate spectral patterns can be derived and adapted to their target location in (and between) the MDCT time/frequency (t/f) grid to seamlessly synthesize high quality sinusoidal tones including sweeps.<br